2024
DOI: 10.1002/smll.202307759
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Droplet Splashing on Positively Skewed Surfaces for High‐Efficiency Evaporation Cooling

Zhaochang Wang,
Xiaojun Liu,
Jiawei Ji
et al.

Abstract: Two types of functional surfaces with the same roughness but completely different surface topographies are prepared, namely positively skewed surfaces filled with micropillar arrays (Sa ≈4.4 µm, Ssk >0) and negatively skewed surfaces filled with microcavity arrays (Sa ≈4.4 µm, Ssk <0), demonstrating promoting droplet splashing. Remarkably, the critical Weber number for generating satellite droplets on the negatively skewed surfaces is significantly lower than that on the positively skewed surfaces, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…When the particle diameter is larger to some extent, the added particles would like the microrolling objects and play a lubrication role at the interface so that the friction coefficient decreases again. The previous studies have confirmed that the coupling effect of surface topography and wettability would provide new ideas for the development of special materials with excellent mechanical durability in complex environments. We also found that the influence of particle wettability on the frictional behavior of rubber sliding interfaces under lubricant conditions is significant. Notably, regardless of particle size, hydrophobic particles in the lubricant result in a lower friction coefficient compared to hydrophilic particles (Figure d).…”
Section: Resultssupporting
confidence: 65%
“…When the particle diameter is larger to some extent, the added particles would like the microrolling objects and play a lubrication role at the interface so that the friction coefficient decreases again. The previous studies have confirmed that the coupling effect of surface topography and wettability would provide new ideas for the development of special materials with excellent mechanical durability in complex environments. We also found that the influence of particle wettability on the frictional behavior of rubber sliding interfaces under lubricant conditions is significant. Notably, regardless of particle size, hydrophobic particles in the lubricant result in a lower friction coefficient compared to hydrophilic particles (Figure d).…”
Section: Resultssupporting
confidence: 65%
“…The gas–liquid interface (GLI) formed between microstructures when a superhydrophobic surface (SHS) is immersed in water effectively reduces flow resistance, , thereby garnering widespread adoption across underwater vehicles, droplet impact, and pipeline transportation. Inspired by the unique properties and wetting behavior of biological surfaces in nature, various advanced biomimetic SHSs have been successfully developed to reduce frictional resistance. ,,, For example, the surface of a conical protrusion structure resembling pufferfish skin decreases the resistance by up to 17.5%, and a surface with a cavity array that mimics fish scales reduces the drag by 4.814% . Similarly, a surface with trapezoidal grooves imitating shark skin demonstrates a drag reduction rate of 6% .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that low surface energy and micro/ nanostructures are the two key factors for superhydrophobic surfaces. 15 Significantly, a micro/nanostructure is very effective in reducing surface friction. 16 Meanwhile, it has been found that reducing surface energy is a useful way of reducing friction coefficients.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The release of 1-dodecanethiol provides a corrosion inhibitor-air cushion that is significantly better than a typical single air cushion of the superhydrophobic surface. It is known that low surface energy and micro/nanostructures are the two key factors for superhydrophobic surfaces . Significantly, a micro/nanostructure is very effective in reducing surface friction .…”
Section: Introductionmentioning
confidence: 99%